2012
DOI: 10.7326/0003-4819-157-7-201210020-00003
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Equations to Estimate Kidney Function in Persons Aged 70 Years or Older

Abstract: Background: In older adults, current equations to estimate glomerular filtration rate (GFR) are not validated and may misclassify elderly persons in terms of their stage of chronic kidney disease. Objective: To derive the Berlin Initiative Study (BIS) equation, a novel estimator of GFR in elderly participants. Design: Cross-sectional. Data were split for analysis into 2 sets for equation development and internal validation. Setting: Random community-based population of a large insurance company. Participants: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
468
7
38

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 526 publications
(532 citation statements)
references
References 53 publications
19
468
7
38
Order By: Relevance
“…6,7,15 Two prior studies in elderly participants suggest that the combination of creatinine and cystatin C provide the most accurate estimates. 10,17 Our results using the CKD-EPI equations are consistent with these studies. We also showed that the combined equation provided the most accurate estimate of prevalence of mGFR,60 ml/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…6,7,15 Two prior studies in elderly participants suggest that the combination of creatinine and cystatin C provide the most accurate estimates. 10,17 Our results using the CKD-EPI equations are consistent with these studies. We also showed that the combined equation provided the most accurate estimate of prevalence of mGFR,60 ml/min per 1.73 m 2 .…”
Section: Discussionsupporting
confidence: 82%
“…[9][10][11][12][13] Current guidelines recommend using the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) equations for GFR estimation in clinical practice or other equations using standardized creatinine and cystatin C if they are more accurate than the CKD-EPI equations. 14 Among other equations, only the Japanese equations, 15,16 the Berlin Initiative Study (BIS) equations, 17 and the Caucasian and Asian pediatric and adult subjects (CAPA) equation 18 are based on standardized creatinine and standardized cystatin C assays. A comparison of the performance of equations developed by these four groups in elderly individuals has not been reported.…”
mentioning
confidence: 99%
“…Second, we classified the subjects by using eGFR. Recently, it has been reported that kidney function might be more accurately assessed by using both serum cystatin and creatinine levels in persons aged 70 years or older (Schaeffner et al, 2012). Thus, the appropriateness of our classification will need to be re‐evaluated in relation to geriatric medicine.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that eGFR Cr-Cys does indeed improve the accuracy of mGFR estimation over eGFR Cr or eGFR Cys in a variety of populations (criterion 1) (4,18,19,44,45). However, eGFR Cr-Cys is inferior to eGFR Cr by another criterion (criterion 3).…”
Section: The Egfr Cr-cys Paradoxmentioning
confidence: 97%